Cigarette Smoking and Pancreatic Cancer Survival - Yuan, Chen (J Clin Oncol, 2017)
PURPOSE: Cigarette smoking is associated with increased incidence of pancreatic cancer. However, few studies have prospectively evaluated the association of smoking with patient survival. PATIENTS AND METHODS: We analyzed survival by smoking status among 1,037 patients from two large US prospective cohort studies diagnosed from 1986 to 2013. Among 485 patients from four prospective US cohorts, we also evaluated survival by prediagnostic circulating levels of cotinine, a metabolite of nicotine that is proportional to tobacco smoke exposure. On the basis of prediagnosis cotinine levels, we classified patients as nonsmokers (< 3.1 ng/mL), light smokers (3.1-20.9 ng/mL), or heavy smokers (≥ 21.0 ng/mL). We estimated hazard ratios (HRs) for death by using Cox proportional hazards models, with adjustment for age, sex, race/ethnicity, body mass index, diabetes status, diagnosis year, and cancer stage. RESULTS: The multivariable-adjusted HR for death was 1.37 (95% CI, 1.11 to 1.69) comparing current smokers with never smokers (P = .003). A statistically significant negative trend in survival was observed for increasing pack-years of smoking (P(trend) = .008), with HR for death of 1.49 (95% CI, 1.05 to 2.10) for > 60 pack-years of smoking versus never smoking. Survival among former smokers was similar to that for never smokers, regardless of time since quitting. Heavy smokers defined by prediagnostic circulating cotinine levels had a multivariable-adjusted HR for death of 1.76 (95% CI, 1.23 to 2.51) compared with nonsmokers. Among patients with circulating cotinine levels measured within 5 years before diagnosis, heavy smokers had a multivariable-adjusted HR for death of 2.47 (95% CI, 1.24 to 4.92) compared with nonsmokers. CONCLUSION: Cigarette smoking was associated with a reduction in survival among patients with pancreatic cancer.